KERAGAAN TINGKAT PENERAPAN METODE SLPTT PADI DI KECAMATAN CIAWI BOGOR - Pepi Rospina Pertiwi; Diarsi Eka Yani (Jurnal Matematika Sains dan Teknologi, 2016)
This research is intended to explain (1) the perception of farmers on the application of rice SLPTT methods, and (2) the level of implementation of rice SLPTTmethod. The study design was descriptive research. The study population were all farmers who were members of paddy farmer groups in the District of Ciawi, who participated in SLPTT. Samples were selected from two groups of SLPTT participants in two villages, each of 20 participants. Data consisted of primary data and secondary data. The perception of farmers on the application of rice PTT was measured on the perception of farmers in terms of the correspondence amongmethods, characteristic of the area, and the message content of innovation. The level of implementation of the rice SLPTT method was measured by the success of the method in delivering innovation, the success of the method of making the farmers applying innovation, and the success of the method in providing benefits to farmers. The results showed that farmers' perception on the suitability of the application of SLPTT methods with the characteristics of the area is quite good, as well as the farmer's perception about the suitability of the application of SLPTT methods with the content of the message is in excellent innovation. The level of implementation of the method is quite effective. Farmers acquire enough knowledge to increase even tend to be greatly increased. In addition, farmers acquire sufficient mastery of skills, take benefits of the increased production and income. Penelitian bertujuan menjelaskan (1) persepsi petani terhadap penerapan metode SLPTT padi, dan (2), tingkat penerapan metode SLPTT padi. Rancangan penelitian adalah descriptive research. Populasi penelitian adalah semua petani yang menjadi anggota kelompok tani padi di wilayah Kecamatan Ciawi, yang menjadi peserta SLPTT. Sampel dipilih dari dua kelompok peserta SLPTT di dua desa, masing-masing 20 orang peserta. Data yang dikumpulkan terdiri dari data primer dan data sekunder. Persepsi petani tentang penerapan PTT padi yang diukur adalah persepsi petani tetang kesesuaian metode dengan karakteristik wilayah, dan isi pesan inovasi. Tingkat penerapan metode SLPTT padi diukur dengan keberhasilan metode dalam menyampaikan inovasi, keberhasilan metode dalam menjadikan petani menerapkan inovasi, dan keberhasilan metode dalam memberikan manfaat bagi petani. Hasil penelitian menunjukkan bahwa persepsi petani tentang kesesuaian penerapan metode SLPTT dengan karakteristik wilayah tergolong cukup baik, persepsi petani tentang kesesuaian penerapan metode SLPTT dengan isi pesan inovasi tergolong sangat baik. Tingkat penerapan metode tergolong cukup efektif baik. Petani memperoleh pengetahuan yang cukup meningkat bahkan cenderung sangat meningkat, memperoleh penguasaan keterampilan yang cukup meningkat serta memperoleh manfaat terhadap produksi dan pendapatan yang juga cukup meningkat.